At the Sources of Indonesian Political Islam's Failure: The Split between the Nahdlatul Ulama and the Masyumi in Retrospect - Madinier, Rémy; Feillard, Andrée (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
This article intentionally emphasizes the analysis of the political context, while touching only slightly on sociological considerations. The fact that the sociological difrerences could be overcome, since the two currents once succeeded in uniting into Masyumi. Moreover, this article wanted to show common notions of basic disagreements, such as the oft-noted conflict where reformists frequently despise traditionalists' penchant for Sufism, for the supernatural and for the irrational, which they consider to be everywhere the